2003
DOI: 10.4319/lo.2003.48.1.0277
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships among Southern Ocean copepods and krill: Some uses and limitations of a stable isotope approach

Abstract: The use of stable isotopes to study food webs has increased rapidly, but there are still some uncertainties in their application. We examined the ␦ 15 N and ␦ 13 C values of Antarctic euphausiids and copepods from the Polar Front, Lazarev Sea, and Marguerite Bay against their foodweb baseline of particulate organic matter (POM). Interpretations of trophic level were helped by comparison with other approaches and by calibration experiments with Euphausia superba fed known diets. Results for well-known mesozoopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 52 publications
12
124
0
Order By: Relevance
“…This was explained by the adults shifting to a more detritivorous diet containing carcasses of the copepod Neocalanus cristatus. Krill larvae are found to be herbivorous and to some extent omnivorous depending on season and species (Daly 1990, Frazer 1996, Meyer et al 2002, Schmidt et al 2003, supporting the general observation of an ontogenetic increase in trophic position. The paradox of the krill Krill have a prey-size spectrum that spans several trophic levels, as indicated by the trophic overlap in stable isotopes documented here.…”
Section: Trophic Position In Relation To Sizementioning
confidence: 78%
See 2 more Smart Citations
“…This was explained by the adults shifting to a more detritivorous diet containing carcasses of the copepod Neocalanus cristatus. Krill larvae are found to be herbivorous and to some extent omnivorous depending on season and species (Daly 1990, Frazer 1996, Meyer et al 2002, Schmidt et al 2003, supporting the general observation of an ontogenetic increase in trophic position. The paradox of the krill Krill have a prey-size spectrum that spans several trophic levels, as indicated by the trophic overlap in stable isotopes documented here.…”
Section: Trophic Position In Relation To Sizementioning
confidence: 78%
“…C caused by lipids (Schmidt et al 2003), as C:N values of all species analysed were near the lower limits of the ranges reported in the literature (Schmidt et al 2003, Kiørboe 2013) and thus indicated low lipid content.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Problems are partly caused by ecosystem complexities such as multiple food sources or variable growth and turnover rates in relation to an isotopically changing food-web baseline (O'Reilly et al 2002, Schmidt et al 2003. There are, however, further problems related to the fundamental principles of the method.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…3F) sustains the hypothesis of a high level of activity and lipid loss in this muscle complex compared with the unchanged C/N ratio during treatment 1 ( Fig. 3C; Schmidt et al 2003, Logan et al 2008). …”
Section: Effects Of Food Treatment On Isotopic Dynamics In the Adductmentioning
confidence: 86%